Systematics of big-eyed bats, genus Chiroderma Peters, 1860 (Chiroptera: Phyllostomidae) - Garbino, Guilherme S. T.; Lim, Burton K.; Tavares, Valéria Da C. (Zootaxa, 2020)
We present a revision of the Neotropical bat genus Chiroderma, commonly known as big-eyed bats. Although species of Chiroderma have a wide distribution from western México to southern Brazil, species limits within Chiroderma are not clearly defined, as attested by identification errors in the literature, and there is no comprehensive revision of the genus that includes morphological and molecular data. Our review is based on phylogenetic analyses of two mitochondrial (COI and CYTB) and two nuclear (RAG2 and DBY) genes, coalescence analyses of mitochondrial genes, and morphological analyses including type specimens of all named taxa. We recognize seven species in three clades: the first clade includes (1) C. scopaeum Handley, 1966, endemic to western México and previously considered a subspecies of C. salvini; and (2) C. salvini Dobson, 1878, a taxon associated with montane forests, distributed from México to Bolivia; the second clade includes (3) C. improvisum Baker and Genoways, 1976, endemic to the Lesser Antilles, and (4) C. villosum Peters, 1860, widely distributed on the continental mainland and polytypic, with subspecies C. v. villosum and C. v. jesupi; and the third clade includes (5) the polytypic C. doriae Thomas, 1891, with C. d. doriae distributed in eastern Brazil and Paraguay, and C. d. vizottoi, occurring in northeastern Brazil; (6) C. trinitatum Goodwin, 1958, distributed from Trinidad to Amazonia; and (7) C. gorgasi Handley, 1960, distributed from Honduras to trans-Andean South America, previously considered a subspecies of C. trinitatum.